Reversible cerebral vasoconstriction syndrome following indomethacin. (December 2014) - Calic, Zeljka; Choong, Ho; Schlaphoff, Glen; Cappelen-Smith, Cecilia
Background: Reversible cerebral vasoconstriction syndrome (RCVS) is characterized by severe thunderclap headaches and transient segmental cerebral arterial vasoconstriction. Precipitating factors, including the postpartum state and exposure to vasoactive substances are identified in approximately 50% of cases. Non-steroidal anti-inflammatory drugs have rarely been associated with RCVS. Case description: We report a case of a 51-year-old female with RCVS after administration of indomethacin given to relieve pain caused by renal colic. Cerebral imaging showed non-aneurysmal cortical subarachnoid hemorrhage, and formal angiography demonstrated widespread multifocal segmental narrowing of medium-sized cerebral arteries. These changes resolved on repeat angiography at 3 weeks. Discussion: Indomethacin is a commonly used drug for treatment of certain primary headache disorders. To date, its mechanism of action remains unclear. A well described side effect of indomethacin is headache, which may be secondary to its vasoconstrictive effects. In our case, we postulate indomethacin, either alone or in combination with emotional stress from pain, triggered or exacerbated an underlying predisposition to RCVS.